El sobrepeso y la obesidad infantil en estudiantes de educación básica de la Escuela Nuevo Amanecer - Gutiérrez Ortiz, Carlos Andrés; Rogel Elizalde, Alexa Milena (Machala: Universidad Técnica de Machala, 2022)
This research work is an integrative project, and focused on childhood overweight and obesity in basic education students of the New Dawn school. Whose goal is oriented in. To determine the causes of overweight and obesity in basic education students of the Nuevo Amanecer school in the 2022-2023 school year. The specific objective Establish the fat level of the students, through an anthropometric table to identify cases of obesity, identify physical activities that help prevent obesity in basic education students and propose recreational activities, directed by teachers of basic education school New Dawn The data collection was based on a quantitative approach, descriptive character, managing to diagnose the reality in the New Dawn school, The data collection was carried out through a field investigation, of the quantitative type and the survey instrument to discover the reality in the New Dawn school. The methods of greatest incidence in this inquiry are the analytical-synthetic and others that were integrated as auxiliaries, such as. comparative and bibliographic, which contributed significantly at the time of collecting information based on the specific objectives, which allow solving the problem in an orderly, sequential manner and integrate the results to settle the necessary criteria when writing the proposal. In relation to the population, all of the teachers and students of the institution were suspected, a survey was selected for its construction, the objects of study were related from which two dimensions were derived and, consequently, the indicators served as a guide for the elaboration of the instruments The analysis of results in the tabulation shows that teachers do not have adequate knowledge.
El presente trabajo de investigación se centró en el sobrepeso y la obesidad infantil en estudiantes de educación básica de la escuela Nuevo Amanecer cuyo objetivo se orienta en determinar las causas del sobrepeso y obesidad en el año lectivo 2022-2023. Se busca establecer el nivel de grasa de los estudiantes mediante una tabla antropometría para identificar casos de obesidad en los estudiantes, identificar actividades físicas que contribuyan a prevenir la obesidad y proponer actividades lúdicas dirigidas a los docentes de educación básica. Se realizó la recopilación de datos por medio de una investigación de campo, del tipo cuantitativo e instrumento la encuesta al diagnosticar la realidad en la escuela Nuevo Amanecer. Los métodos de mayor incidencia en esta indagación es el analítico-sintético y otros que se integraron en calidad de auxiliares, como, comparativo y bibliográfico, mismos que aportaron significativamente al momento de recabar la información con base a los objetivos específicos, mismos que permiten solventar la problemática en forma ordenada, secuencial e integrar los hallazgos para dirimir los criterios necesarios al redactar la propuesta. En relación con la población se consideró a todos los docentes y estudiantes de la institución, se seleccionó encuesta para su construcción, se relacionaron los objetos de estudio de donde se derivaron dos dimensiones y en consecuencia los indicadores sirvieron de guía para la elaboración de los instrumentos. El análisis de resultados en la tabulación demuestra que los docentes no tienen conocimientos adecuados.
Keywords: OBESIDAD INFANTIL; ACTIVIDAD FISICA; EDUCACION BASICA; ESCUELA